2017
DOI: 10.1186/s13018-017-0611-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy assessment of measuring component position after total ankle arthroplasty using a conventional method

Abstract: BackgroundThis study was to assess the accuracy of measuring the tibial and talar components position and to investigate the outlier rate of each component and predisposing factors related to component malalignment after total ankle arthroplasty (TAA) using a conventional method.MethodsOne hundred fifty consecutive primary total ankle arthroplasty were performed using the three-component HINTEGRA prosthesis for ankle end-stage osteoarthritis. Radiographic analysis for the accuracy of component position in coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…12,15 Despite improvements in preoperative planning tools and instrumentation, restoring the ankle’s axis of rotation by resurfacing the tibial and talar surfaces remains challenging. 7,21,27 Over the past decade, mobile-bearing total ankles were introduced to the market and showed satisfactory outcomes. 2,3,5,9,10,30,33-35 Adding an interface between the polyethylene insert (PI) and the tibial component potentially permits motion between the talus and PI in both the sagittal and coronal planes and may allow rotational motion (axial plane).…”
mentioning
confidence: 99%
“…12,15 Despite improvements in preoperative planning tools and instrumentation, restoring the ankle’s axis of rotation by resurfacing the tibial and talar surfaces remains challenging. 7,21,27 Over the past decade, mobile-bearing total ankles were introduced to the market and showed satisfactory outcomes. 2,3,5,9,10,30,33-35 Adding an interface between the polyethylene insert (PI) and the tibial component potentially permits motion between the talus and PI in both the sagittal and coronal planes and may allow rotational motion (axial plane).…”
mentioning
confidence: 99%
“…96 Lee et al performed radiography immediately postoperatively, at 3 months, 6 months, 1 year, and then annually. 97 Immediate postoperative anteroposterior (AP) and lateral radiographs are helpful in determining whether the bones and orthopaedic implants are in expected alignment. They are also adequate in establishing a baseline alignment for future assessments.…”
Section: Imaging Strategymentioning
confidence: 99%
“…However, they are performed without weightbearing, and attention to proper positioning will ensure these radiographs are useful as a comparison study for future examinations. 97 Subsequent studies are performed with AP and lateral weightbearing technique depending on patient tolerance, and some institutions include lateral non-weightbearing maximally dorsiflexed and plantarflexed images to assess the range of motion. 98 The subsequent studies are used to evaluate for signs of osteointegration, determine osseous and prosthetic component alignment, and detect developing heterotopic ossification, in addition to evaluating range of motion.…”
Section: Imaging Strategymentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] Various predisposing factors including age, gender, and preoperative deformity can affect the outcome of TAA. [9,11,[17][18][19][20][21] In related to gender difference, several studies demonstrated divergent clinical outcomes following total hip or total knee arthroplasty. In total hip arthroplasty, some studies reported no difference in all postoperative outcome measures between men and women.…”
Section: Introductionmentioning
confidence: 99%